Absence of Localization of Fourier-Laplace Series - bin Rasedee, AFN; Rakhimov, A; Ahmedov, AA; Ishak, N; Hamzah, SR (Amer Inst Physics, 2024)
This article investigates a function f (x), constructed from the Nikol'skii class in S-2. The estimation obtained will show that the Riesz mean of the spectral expansions is unable to be strengthened due to absence of localization caused by a singualrity at a definite point f (x), on the sphere.